PELAKSANAAN KAMPANYE POSITIF MENJELANG PEMILU BERDASARKAN PKPU NO. 23 TAHUN 2018 TENTANG KAMPANYE PEMILIHAN UMUM - mawar, hakimah (Siyasyatuna | Jurnal Hukum Tata Negara, 2023)
Indonesia is a country that upholds democracy so that in determining the government it will be through general elections (elections). The implementation of the general election (election) which took place in 1999 was the first implementation of the general election (election) during the reform period which used a balanced representation system (proportional) with a basic system and the principle of fairness and equity. Campaigns have various types of campaigns in addition to the various types of campaigns in the campaign there are also prohibitions based on the mandate of the Law governing campaigns while the purpose of the prohibition is to create campaign methods so that they are more organized without eliminating the objectives of the campaign itself. That is why this article intends to investigate the extent to which the implementation of these campaign activities has been carried out positively, in accordance with the current flow, especially in the run-up to the holding of simultaneous general elections in the coming political years. Meanwhile, the things that will be discussed in this study are: 1) How is the implementation of the campaign in the general election (election)?; 2) What are the provisions for campaign implementation based on KPU Regulation Number 23 of 2018 in regulating the ongoing general election campaign (election)? This research uses a type of qualitative research with a descriptive approach. Namely, researchers will describe campaign media in general elections based on PKPU Number 23 of 2018 concerning General Elections. This research is library research or research using library research methods.